24-h Cardiac Autonomic Profile after Exercise in Sedentary Subjects - Peçanha, T.; Prodel, E.; Bartels, R.; Nasario-Junior, O.; Paula, R. B.; Silva, L. P.; Laterza, M. C.; Lima, J. R. P. (International Journal of Sports Medicine, 2014)
Most studies regarding the impact of exercise intensity on cardiac autonomic regulation were conducted with athletes and used exercise intensities exceeding those recommended by position stands. We evaluated the influence of exercise intensity in a typical ACSM-aerobic session on 24-h cardiac autonomic modulation in sedentary subjects. Ten healthy sedentary subjects participated in the 3-day study. On 2 days, subjects performed a moderate- or high-intensity aerobic exercise session (MI, HI). The post-exercise protocol consisted of a continuous electrocardiographic recording for 1 h at the laboratory plus 23 h under ambulatory conditions. On the third day 24-h electrocardiographic recording was done without prior exercise (NPE). Heart rate (HR) and frequency-domain parameters (LF, HF) of heart rate variability were evaluated during the entire recovery period. Higher values of HR and lower values of HF and LF were observed throughout the first hour after the HI compared with the MI session. This difference was not observed after in ambulatory awake condition, but reappeared during sleep, when HF values after HI were lower compared with the NPE and MI (p<0.05). Even within the submaximal intensity-range of a typical exercise session, the intensity of exercise influences the post-exercise cardiac autonomic modulation in sedentary subjects.
Keywords: heart rate control; autonomic nervous system; holter monitoring